Bibliometric Analysis of Learning Models and Physical Education Based on Scopus Data - Andika Triansyah; Yusi Riksa Yustiana; Ani Kurniawati; Suci Lukitowati (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
This study aims to explore the literature on learning models in physical education based on scopus indexed articles. The research method used to conduct the analysis is bibliometric. Search and filtering strategy using PRISMA flow chart. The research review uses data in comma-separated values (CSV) format, which is then exported to Microsoft Excel and to visualize the search results of bibliometric analysis the tool used is VOSviewer. The analysis resulted in the development of publications in the domain of learning models in physical education experiencing an increasing trend from year to year. Goodyear, V.A became the most prolific author by publishing as many as 5 research documents. The influential researcher with the most citations was written by Goodyear & Casey in 2015 (134 citations), the title of the article Innovation with change: developing a community of practice to help teachers move beyond the 'honeymoon' of pedagogical renovation. During the period 2012-2023, Indonesia became the country that has conducted the most research publications on the topic of learning models in physical education. While the country with the most citations is the United Kingdom with a total of 422 citations. The keywords that appear most in search analysis are physical education, learning model, cooperative learning, physical activity, e-learning, pedagogy, soccer, learning, motivation, and motor learning. The conclusion of the study resulted in the development of publication of learning models in physical education in the 2012-2023 period tended to increase.